PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK CONCEPTUAL UNDERSTANDING PROCEDURES UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA - Gummah, Syifaul; Soraya, Liza Hani; Ahzan, Sukainil; Hardariyanti, Hardariyanti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
This study aims to improve learning outcomes and activities of students of class VIII SMPN 13 Mataram through Cooperative Learning Model Conceptual Understanding Procedures (CUPs). This research is a classroom action research consisting of 2 cycles containing planning, implementation, observation, evaluation and reflection. The population of this study is all students of class VIII SMP Negeri 13 Mataram which amounted to 3 classes. The sample of this research is the students of class VIII-E. Research approach used qualitative and quantitative. The research instruments used were obsevation and study test. Data obtained, analyzed by using analysis mastery learning. The results of the research, in the cycle I classical completeness of 72.09% (not complete). Teachers are categorized as ’very active’ and students are categorized as ’active’. In the second cycle, the percentage of grade mastery is 86.04%. Teachers are categorized as ’very active’ and active students are categorized as ’active’. Student learning outcomes increased by 13.09%. We conclude that applying cooperative learning model of Conceptual Understanding Procedures (CUPs) techniques can improve student learning outcomes and activities